Pengaruh Self-Control terhadap Perilaku Cyberslacking pada Mahasiswa Gen Z - Thari Margaretha; Maria Goretti Adiyanti (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2026)
This study aims to analyze the effect of self-control on cyberslacking behavior among Generation Z university students. The research is grounded in the phenomenon of increasing internet use in academic settings, which on the one hand supports the learning process, but on the other hand has the potential to encourage non-academic internet use during lectures. This study employed a quantitative approach with a correlational design, using purposive sampling involving 130 Generation Z students who actively use the internet for academic activities. Data were collected using a self-control scale based on Averill’s aspects and a cyberslacking scale based on the aspects proposed by Albar and Ariyanto. Data analysis was conducted using simple linear regression. The results indicated a significant negative effect of self-control on cyberslacking behavior (R = 0.686; p < 0.05), with a contribution of 47.1%. The higher the level of self-control possessed by students, the lower their tendency to engage in cyberslacking behavior, and vice versa. These findings reinforce the view that self-control plays an important role in regulating maladaptive internet use during the learning process. This study is expected to provide practical implications for students and educational institutions in efforts to enhance self-control in order to minimize cyberslacking behavior in academic environments.